Alcance de los requisitos de la norma ISO 14001:2015 como estrategia de mejoramiento operacional del sector de hidrocarburos en Colombia. (2021)
In Colombia's hydrocarbons industry, and in particular oil production service providers, they generate amounts of environmental aspects and impacts related to inadequate management of hazardous solid waste and which, in this case, oily waste "erases", should be considered as an environmental threat if the application of technologies and management programmes are not properly implemented. In this way, the orientation of the requirements of ISO 14001:2015 as a tool of continuous improvement for organizations, allowed the scope of an environmental management system that, in the first instance as the greatest element, will organize the environmental objectives, according to its context in order to reduce the risks of the hydrocarbon extraction operation, of this activity.